(3GdJYhjV Yf GdNWC GdbVGFi (B: s (3OQGSI ebGQfI ai GdbGfhf GdeUQi h GdadSWjfi (B/ s - (3hdjO YjSi ehSi YHjGJs; (3eMeO SGei YHOGdUGObs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2021)
(3jYJHQ ehVhY GdJYhjV Yf GdNWC GdbVGFj ef Cge GdehGVjY GdJj Jge bWGY GdYOGdI HcGaI echfGJg; h ef GdehGVjY GdegeI h GdMSGSI ai PGJ GdhbJ dcd ehGWf; fJjLI GfJTGQ GdCNWGA GdbVGFjI GdLSjeI GdJj dG jecf JOGQcgG; ceG Gf GdGJLGgGJ GdabgjI GdMOjKI JHfJ hOYJ dGbQGQ eSDhdjI GdOhdI Yf CNWGA GdSdWI GdbVGFjI; MjK CgejI GdSdWI GdbVGFjI h MGLI GdfGS dgG OYJ GdHGMK dgPg GdOQGSI; EdG Cf GdNdGa Hjf GdhGbY GdfXQj h GdYedj deSCdI JYhjV GdOhdI Yf NWC GdbGVj h fOQI GdGMcGe GdbVGFjI cGfJ Cge GdYbHGJ(B. (3dGRGd GdbVGA hGdabg GdeUQj eNdUG dbGYOI YOe eSDhdjI GdOhdI Yf CNWGA GdbVGA GdG aj CVjb GdeLGdGJ ; YdeG Cf GdbVGA h Gdabg aj GdOhd GdYQHjI jfXQ Gdi eUQ HCfgG QCS GdgQe GdbGfhfj aj GdhWf GdYQHj; h HGdJGdj df JJHfi GdOhd GdYQHjI eSDhdjI GdOhdI Yf GdNWC GdbVGFj eGde jJe JHfjg ef bHd GdbVGA h Gdabg GdeUQj(B. (3h HfGkA Ydi eG JbOe CUHM gfGc VQhQI edMI ddeMGaXI Ydi Mbhb VMGjG GdCNWGA GdbVGFjI MJi dG JgJR KbI GdehGWf HGdbVGA GdPj jTcd GdedLC GdCNjQ GdPj jdhP Hg GdehGWf HMKG Yf GdYOd hQaY GdXde Yfg; h dJchf gPg GdMeGjI GdbGfhfjI QGOYG ef GdhbhY aj GdNWC GdbVGFj GdLSje GdPj bO jOeQ GdGSQI hGdeLJeY(B. (3h dMjf JHfi gPg GdMeGjI h dSO Gj aQGZ JTQjYj h abgj dGHO ef EbQGQ fXGe GdJCejf Ydi GdeSDhdjI GdeOfjI ddbGVj ef NdGd EfTGA UfOhb dJYhjV GdeJVQQ ef GdNWC GdbVGFis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2021s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B303-334s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdeOfjs; (3GdJYhjVs; (3GdNWC GdbVGFi s; (3GdYed GdbVGFjs; (3GdJMcje s; (3GdJRGeGJ GdbVGIs; (3GdfXGe GdGfLdh GeQjcjs; (3GdJYSa ai GSJYeGd GdSdWI GdbVGFjIs; (3GdNWC Gdegfj GdLSjes; (3GdeSFhdjI GdTNUjI ddbVGIs; (3GdGfXeI GdbGfhfjI GddGJjfjIs; (3eSFhdjI GdOhdI Yf GdNWC GdbVGFjs; (3GdbGfhf GdadSWjfjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs